Quercetin, a flavonoid, combats rotavirus infection by deactivating rotavirus-induced pro-survival NF-κB pathway - Banerjee, Shreya; Sarkar, Rakesh; Mukherjee, Arpita; Miyoshi, Shin-ichi; Kitahara, Kei; Halder, Prolay; Koley, Hemanta; Chawla-Sarkar, Mamta (Frontiers in Microbiology, 2022)
Rotavirus (RV) is the leading cause of acute gastroenteritis and watery diarrhoea in children under 5 years accounting for high morbidity and mortality in countries with poor socio-economic status. Although vaccination against RV has been implemented in more than 100 countries, the efficacy of vaccine has been challenged in low-income settings. Lack of any FDA approved drug against RV is an additional concern regarding the treatment associated with rotavirus-induced infantile death. With the purpose for the discovery of anti-RV therapeutics, we assessed anti-rotaviral potential of quercetin, a well characterized antioxidant flavonoid. In vitro study revealed that quercetin treatment resulted in diminished production of RV-SA11 (simian strain) viral particles in a concentration dependent manner as estimated by the plaque assay. Consistent with this result, western blot analysis also revealed reduced synthesis of viral protein in quercetin treated RV-SA11 infected MA104 cells compared to vehicle (DMSO) treated controls. Not surprisingly, infection of other RV strains A5-13 (bovine strain) and Wa (Human strain) were also found to be abridged in the presence of quercetin compared to DMSO. The IC50 of quercetin against three RV strains ranges between 2.79 - 4.36 μM and S.I. index is greater than 45. Concurrent to the in-vitro results, in-vivo study in mice model also demonstrated reduced expression of viral proteins and viral titre in the small intestine of quercetin treated infected mice compared to vehicle treated infected mice. Furthermore, the result suggested anti-rotaviral activity of quercetin to be interferon independent. Mechanistic study revealed that the antiviral action of quercetin is co-related with inhibition of RV-induced early activation of NF-κB pathway. Overall, the present study delineates the strong anti-RV potential of quercetin and also proposes it as future therapeutics against rotaviral diarrhoea.